Spectral Efficiency Performance Analysis of UL Linear Precoding in Massive MIMO Systems with S-MMSE and MMMSE - Soualah Badr Eddine; Ajgou Riadh (University Of Eloued جامعة الوادي, 2020)
The 5G network encompasses a set of technologies corresponding to the fifth generation of the standard for mobile telephony. It is validated by the ITU, the International Telecommunication Union. Among these technologies is massive MIMO. The most important concern is improving spectral efficiency. Massive MIMO systems use large arrays of antennas at the base station to transmit multiple users on the same time-frequency resource. The goal of this paper is to maximize the spectral efficiency with linear precoding. In this work, we analyzed the performance and the effect of the minimum mean square error (MMSE), which is a technique of linear precoding on the massive MIMO uplink spectral efficiency in two scenarios: single-cell and multi-cell. We have focused the multi-cell for the reason that it suffers from pilot contamination problems. Orthogonal pilot sequences have to be reused among cells; this leading to estimation errors of channel state information in both the transmitter and the receiver, The MMSE technique is used to overcome the interference that limits the spectral efficiency for massive MIMO system. We apply two MMSE algorithms explicitly S-MMSE and M-MMSE.
Intervention
Keywords: 5G; massive MIMO; spectral efficiency; pilot contamination